Social factors that affect the acceptability of the enviro loo sanitation technology: a case of schools in Limpopo Province - Tshivhase, Ndiafhi Jeremiah (University of Limpopo, 2016)
The purpose of this study was to investigate the social factors that affect the acceptability of the Enviro Loo sanitation technology in schools. The study adopted the anti-positivism theory. Phenomenology school of thought was used as one of the three schools of thoughts as marked under Anti-positivism. The qualitative research method had its foothold in the fact that social factors, as a human activity, occurs in a particular natural and social environment. Utilising the qualitative research design, the researcher focused on describing and understanding the social factors that influence the acceptability of the Enviro Loo sanitation technology at schools. The study utilised an interview guide to collect data. The advantage of this is that it allowed the researcher to probe and ask for clarification of some answers as given by the respondents The population of this study comprised 35 secondary schools in Limpopo Province that benefited from the implementation of the Enviro Loo sanitation technology system during the 2010/11 financial years. Non-probability sampling was used. The method used to select the schools was convenience sampling as a non-probability sampling technique where subjects are selected because of their convenient accessibility and proximity to the researcher. This is because the researcher was bound by time, money and workforce and because of these limitations, it was almost impossible to randomly sample the entire population. Three sets of focus groups were used as sample, namely; the Provincial Sanitation Task Team (PSTT), School Governing Body (SGB) and Leaner’s Representative Council (LRC). All groups were gender balanced and members participated voluntarily. Nvivo was utilised to analyse data. The audio recordings from the digital voice recorder were transcribed, translated into English, typed into word and thematic analysis was used.
Thesis (M. Dev.) --University of Limpopo, 2016
Keywords: Enviro Loo sanitation technology; Schools sanitation; Sanitation; School hygiene; Toilets; Sanitation -- South Africa